EFEKTIVITAS KOMUNIKASI PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK TUPPERWARE - Nurnawati Hindra H, Triana Puspa Dewi, Maya Sekar Wangi & (Transformasi, 2017)
One of the products that uses personal selling is tupperware .Personal selling is considered veryeffective to affect consumers in taking resolve. The purpose from the study is to prove ishypothesized how major personal communications selling effectiveness of the decision thepurchase of products tupperware at the sidanegara , case .Quantitative methods eksplanatorywith the kind of research .The correlation product moment obtained correlation value of 0,784 .Correlation value this means is the personal communications selling effectiveness of thedecision the purchase of product.Key words: The effectiveness of communication , personal selling , decision to purchase